Trichomonas vaginalis: Diagnosis and Clinical Characteristics in Pregnancy. Issue 5 (1994) - Heine, R. Phillip; McGregor, James A.; Patterson, Elisa; Draper, Deborah; French, Janice; Jones, Ward
Abstract : Objective: The objectives of this study were to 1) determine the prevalance and characterize the symptomatology of Trichomonas vaginalis (TV) infection in pregnant women on entry into prenatal care in an inner-city population; 2) compare conventional microscopic methods vs. culture techniques in diagnosing TV in both symptomatic and asymptomatic pregnant patients; and 3) correlate wet mount microscopic and microbiologic characteristics of varying manifestations of trichomoniasis. Methods: One thousand two hundred sixty patients in an inner-city population were tested at entry into prenatal care for TV by saline wet mount and culture techniques. Other tests for lower genital tract infection were also performed. Vaginal symptoms were ascertained through standardized questioning prior to examination. Standard microscopic and microbiologic data were also obtained for analysis. Wet mounts were systematically examined and considered negative if no TV was identified in 10 high powerfields (HPFs). Cultures were inspected from days 4 to 7 or until positive results were obtained. Results were analyzed using McNemar's test for correlated proportions, chi-squared test, or Fisher exact test where appropriate. Results: Culture and wet mount results were available in 1, 175 patients. TV infection was documented by one or both techniques in 110/1, 175 (9.4%). Culture methods detected 105/110 (94.5%) of all patients while wet mount detected 90/110 (73%) ( P <0.001). Vaginal symptoms were present in only 20/110 patents (18.2%). Among asymptomatic patients, culture detected 94% while wet mount detected 70% ( P < 0.001). Among symptomatic patients, wet mount and culture were both effective and diagnosed 85% and 95% of infections, respectively ( P = not significant). Patients with TV were more likely to have increased vaginal fluid wlaite blood cells (WBCs) and more severe vaginal flora disruption than uninfected controls. Subgroup analysis revealed wet mount-positive/culture-positive patients were more likely to have vaginal flora disruption, as evidenced by decreased lactobacilli and elevated vaginal pH, than wet mount-negative/culture-positive subjects. Coexistent infection rates were similar regardless of wet mount status. Elevated vaginal fluid WBCs were more common among patients with symptoms. Conclusions: 1) Screening pregnant women for TV based solely on symptomatology is ineffective in this population; 2) culture techniques detected more infections than conventional microscopic evaluation; and 3) significant increases in vaginal fluid WBCs and altered vaginal flora are found in both symptomatic and asymptomatic TV, suggesting that both infestations have the potential to adversely affect pregnancy outcome. Studies on the influence of TV on pregnancy outcomes are ongoing.